Analysis of Husband-Wife Interaction, Financial Vulnerability, and Objective Well-Being in Sandwich Generation Families - Jihan Apikasari Putri; Johan, Irni Rahmayani; Yuliati, Lilik Noor (PT Inovasi Pratama Internasional, 2024)
In sandwich-generation families, there are individuals who simultaneously support the financial needs of children and the elderly. This is a quantitative study with a cross-sectional design using an online survey as a data collection tool. The study was conducted in Indonesia with a research population including sandwich families living in one house consisting of three generations: husband and wife, children, and elderly. The research sample consisted of working wives from the sandwich generation. Of the 223 respondents who participated, 106 met the criteria for further analyses. The results show that spousal education and income play important roles in reducing financial vulnerability and improving family welfare. Harmonious interactions between husbands and wives can reduce financial vulnerability and improve family welfare. Conversely, high financial vulnerability can disrupt a family's objective welfare if not properly managed. The conclusion is the need to improve financial literacy, create a good financial management strategy, and maintain open and harmonious communication between husband and wife to reduce financial vulnerability and improve the welfare of sandwich-generation families.